2017
DOI: 10.1177/0032321717742835
|View full text |Cite
|
Sign up to set email alerts
|

Fear of Electoral Violence and its Impact on Political Knowledge in Sub-Saharan Africa

Abstract: The literature on electoral violence has focused on its causes as well as its scope, ignoring the implications for citizens trying to practice their political citizenship. Informed citizens are a central part of a functioning democracy. The emotive response to violence may play an important role here. This article contributes to a deeper understanding of how the voter responds to violence. Recent work on the role of emotions in politics has demonstrated its positive role for cognition, as fear can increase the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 76 publications
(93 reference statements)
0
9
0
1
Order By: Relevance
“…The largest body of work focuses on effects on behavior, in particular turnout (Bekoe & Burchard, 2017; Bratton, 2008; Burchard, 2015; Höglund & Piyaranthne, 2009). More recently, research has examined the effects of violence on political attitudes, including satisfaction with democracy (Burchard, 2015), trust and social capital (Dercon & Gutiérrez-Romero, 2012; Höglund & Piyarathne, 2009), and political knowledge (Söderström, 2018). Some studies have examined more aggregate-level consequences of violence, including for incumbent victory (Hafner-Burton, Hyde & Jablonski, 2018), for vote shares (Alesina, Piccolo & Pinotti, 2018; Condra et al, 2018), and for political speech (Alesina, Piccolo & Pinotti, 2018).…”
Section: What We Know About Electoral Violencementioning
confidence: 99%
“…The largest body of work focuses on effects on behavior, in particular turnout (Bekoe & Burchard, 2017; Bratton, 2008; Burchard, 2015; Höglund & Piyaranthne, 2009). More recently, research has examined the effects of violence on political attitudes, including satisfaction with democracy (Burchard, 2015), trust and social capital (Dercon & Gutiérrez-Romero, 2012; Höglund & Piyarathne, 2009), and political knowledge (Söderström, 2018). Some studies have examined more aggregate-level consequences of violence, including for incumbent victory (Hafner-Burton, Hyde & Jablonski, 2018), for vote shares (Alesina, Piccolo & Pinotti, 2018; Condra et al, 2018), and for political speech (Alesina, Piccolo & Pinotti, 2018).…”
Section: What We Know About Electoral Violencementioning
confidence: 99%
“…There are at least three reasons for this: (1) because exposure to political violence might have caused some voters to seek out more independent and local political information, (2) newspaper readers might be more fearful of election violence because they are more exposed to news about crime and violence, not because they are more informed, and (3) because of the timing of the AFB6, we have to rely on events from past rather than future elections. First, several empirical studies have shown that past experience of violence motivates individuals to seek more information (Badiuzzaman & Murshed, 2014; Soderstrom, 2018) and to boost their political engagement, especially in terms of participation and community leadership (Blattman, 2009; Bellows & Miguel, 2009). To assess this issue, we instrument newspaper readership via location-specific Protestant mission density in the early 20th century.…”
Section: Empirical Analysismentioning
confidence: 99%
“…Much of the theoretical and empirical research in the field has sought to assess when and where election violence will occur, rather than what effects it has, with several important exceptions. Recent studies analyze correlations between pre-election violence and subsequent turnout (Bekoe & Burchard, 2017), ruling party vote share (Young, 2016), and political attitudes, beliefs, and knowledge (Linke, 2013; Söderström, 2017). Yet, little of this research is based on methodologies that enable estimates of causal relationships between violence and subsequent behavior.…”
Section: Introductionmentioning
confidence: 99%